2001
DOI: 10.1002/jmri.1209
|View full text |Cite
|
Sign up to set email alerts
|

Safety of metallic implants in magnetic resonance imaging

Abstract: Magnetic resonance (MR) imaging has become a commonly accepted medical procedure. Manufacturers of medical implant devices are submitting claims that their devices are safe and effective in a MR environment. This paper concentrates on the issue of heating of patients due to the interaction of metallic implants with the strong radiofrequency (RF) magnetic field produced by the MR scanner. The commercially available program XFDTD was used to calculate the specific absorption rate (SAR) distribution in a realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 9 publications
2
49
0
1
Order By: Relevance
“…Electrical properties such as the magnetic susceptibility, electrical resistivity, and thermal conductivity of metal materials of the implant have a significant influence on heat production. Other factors include the implant's size, shape, and orientation relative to the direction of the magnetic field, the magnetic field strength, and RF pulse duration and duty cycles [6,12]. In cases where the implant is elongated, the heat pri- marily concentrates at the tip of the implant, and such a heat concentration point is called a "hot spot" [6,12].…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical properties such as the magnetic susceptibility, electrical resistivity, and thermal conductivity of metal materials of the implant have a significant influence on heat production. Other factors include the implant's size, shape, and orientation relative to the direction of the magnetic field, the magnetic field strength, and RF pulse duration and duty cycles [6,12]. In cases where the implant is elongated, the heat pri- marily concentrates at the tip of the implant, and such a heat concentration point is called a "hot spot" [6,12].…”
Section: A B Cmentioning
confidence: 99%
“…Other factors include the implant's size, shape, and orientation relative to the direction of the magnetic field, the magnetic field strength, and RF pulse duration and duty cycles [6,12]. In cases where the implant is elongated, the heat pri- marily concentrates at the tip of the implant, and such a heat concentration point is called a "hot spot" [6,12]. It has been shown that the tip of small metallic wire causes a major temperature rise in a static magnetic field of 1.5T [6].…”
Section: A B Cmentioning
confidence: 99%
“…For bare catheters, the obtained temperature rise ranges from 1 to 28 °C depending on the catheter length and position. Moreover, a commercially available computer aided design (CAD) has been used for evaluating the SAR distribution produced in a realistic human model by a coarse catheter model (1 cm diameter, 8 cm length) implanted in the heart region (Ho, 2001). With this model, a peak SAR averaged over 1 g of 2 W/kg near the metallic implant (compared to the value of 1.8 W/kg at the same location without the metallic implant) has been computed and no appreciable heating has been obtained.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The most used is a simple bare cylindrical copper wire (see Fig. 11a) with various diameters and lengths (Ho, 2001;Golombeck & Dossel, 2004;Stuchly et al, 2006;Pisa et al, 2008), while a more realistic version is constituted by a copper wire covered with plastic (see Fig. 11b).…”
Section: Catheter Modelsmentioning
confidence: 99%
“…The dimensions, orientation, shape, and location of the metallic implant all play a role. 4 Finally, exposure to the electromagnetic field used by CMR scanners may inhibit or modify the operational or functional settings of an electronic implant.…”
Section: Magnetic Field Interactionsmentioning
confidence: 99%